2006
DOI: 10.1016/j.metabol.2005.06.022
|View full text |Cite
|
Sign up to set email alerts
|

Combining β-adrenergic and peroxisome proliferator–activated receptor γ stimulation improves lipoprotein composition in healthy moderately obese subjects

Abstract: Current pharmacological regimens for hypertriglyceridemia and low high-density lipoprotein (HDL) are limited to the peroxisome proliferator-activated receptor (PPAR) alpha activating fibrates, niacin, and statins. This pilot study examined the impact of simultaneous stimulation of cyclic adenosine monophosphate with a beta-adrenergic agonist and PPARgamma with pioglitazone (PIO) on lipoprotein composition in moderately obese, healthy subjects. Subjects were treated with PIO (45 mg) to stimulate PPARgamma or a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2007
2007
2013
2013

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 35 publications
0
10
0
Order By: Relevance
“…For example, lipoprotein lipase (LPL) was upregulated after cAMP (17) and PPAR-␥ (18,19) activation. Combined therapy with ephedrine plus caffeine/pioglitazone (ECPio) significantly reduced plasma triglycerides (triglycerides), VLDL, and LDL levels while it increased HDL total mass (20). Our and several previous results demonstrated that PPAR-␥ activation increases body weight and the expression of several genes involved in mitochondrial biogenesis and lipid metabolism in subcutaneous fat obtained from subjects with type 2 diabetes (18,20 -22).…”
mentioning
confidence: 50%
See 1 more Smart Citation
“…For example, lipoprotein lipase (LPL) was upregulated after cAMP (17) and PPAR-␥ (18,19) activation. Combined therapy with ephedrine plus caffeine/pioglitazone (ECPio) significantly reduced plasma triglycerides (triglycerides), VLDL, and LDL levels while it increased HDL total mass (20). Our and several previous results demonstrated that PPAR-␥ activation increases body weight and the expression of several genes involved in mitochondrial biogenesis and lipid metabolism in subcutaneous fat obtained from subjects with type 2 diabetes (18,20 -22).…”
mentioning
confidence: 50%
“…The characteristics of the study population were previously reported (20). Subjects were healthy and not taking thiazolidinediones, ␤-blockers, orlistat, sibutramine, ephedrine, phenylpropanolamine (Dexatrim), corticosteroids, statins, fibrates, cholesterol-binding drugs, or herbal supplements containing ephedrine and/or caffeine; abusing alcohol; or using other illicit drugs.…”
Section: Research Design and Methods -Nondiabetic Patientsmentioning
confidence: 99%
“…PPARg-mediated signal transduction pathways in adipose tissue (Sell et al, 2004;Hughes et al, 2006;Bogacka et al, 2007). However, to our knowledge, no data on the synergistic effects of PPARg and b2-adrenoceptor agonists on airway smooth muscle in vivo and in vitro have been reported before the present study.…”
Section: Figurementioning
confidence: 69%
“…Noteworthy, we showed the presence of PPARγ both in control and desensitized airway smooth muscle tissues, a condition that may offer a pharmacodynamic basis for the use of PPAR targeting strategies in combination with β 2 ‐adrenoceptor agonists. Several lines of evidence suggest the existence of cross‐talk between the sympathetic nervous system and PPARγ‐mediated signal transduction pathways in adipose tissue (Sell et al ., 2004; Hughes et al ., 2006; Bogacka et al ., 2007). However, to our knowledge, no data on the synergistic effects of PPARγ and β 2 ‐adrenoceptor agonists on airway smooth muscle in vivo and in vitro have been reported before the present study.…”
Section: Discussionmentioning
confidence: 99%
“…28 Paradoxically, simultaneous activation of PPARg and b-adrenergic receptors exhibits synergistic favorable effects on lipoprotein composition. 29 The hemodynamic responses elicited by PPARg are also modulated by b 2 -adrenergic signaling. 30 Moreover, procaterol (a synthetic b 2 -adrenergic agonist) modulates eosinophil function by increasing PPARg expression.…”
Section: Discussionmentioning
confidence: 99%